State-of-the-Art Frequency Control Strategy Based on an Optimal Fuzzy PI-FOPDFλ for SMES and UPFC Integrated Smart Grids Using Zebra Optimization Algorithm - Ghadi, Yazeed Yasin; Neamah, Nabeel Mohammed; Hossam-Eldin, Ahmed A.; Alqarni, Mohammed; AboRas, Kareem M. (IEEE access, 2023)
This article presents a unique controller combining fuzzy proportional-integral (PI) and fractional-order proportional-fractional filtered derivative action (FOPDF ^ {λ } ) with the intention of improving the frequency performance of a hybrid interconnected dual-area power grid incorporating a unified power flow controller (UPFC) and superconducting magnetic energy storage (SMES) devices in the two regions. In the proposed fuzzy PI-FOPDF ^ {λ } controller, the positive aspects of fuzzy logic control (FLC), PI, and FOPD regulators, as well as the added flexibility afforded by fractional calculus for the derivative filter, have all been incorporated. The authors used a recently developed metaheuristic optimization strategy (i.e., the Zebra Optimization Algorithm, or ZOA) to fine-tune the suggested controller parameters for the two-area hybrid power grids studied in this paper. The system model depicts physical constraints, such as the reheat turbine and the generation rate constraint (GRC). The superiority of ZOA is demonstrated by comparing its results to those of the recently developed optimizations Osprey Optimization Algorithm (OOA) and Jellyfish Search Optimizer (JSO). By comparing the performance of the proposed ZOA-based fuzzy PI-FOPDF ^ {λ } controller to that of existing ZOA-tuned fuzzy-based controllers (such as fuzzy PIDF and fuzzy PIDD2), it has been demonstrated that the proposed controller is more effective. In order to achieve higher levels of system stability and validate the robustness of the proposed fuzzy PI-FOPDF ^ {λ } controller, various load patterns were applied to the investigated power system. Step load fluctuation (SLF), pulse load fluctuation (PLF), and sinusoidal wave load fluctuation (SWLF) were among these load patterns. In addition, non-conventional sources such as wind turbines and solar photovoltaic (PV) units have been incorporated into the power system. In addition, a test scenario has been developed to demonstrate how the SMES and UPFC units enhance the overall efficacy of the system. MATLAB simulation results indicate that the proposed fuzzy PI-FOPDF ^ {λ } controller, which is based on the ZOA, has the potential to enhance system stability despite the aforementioned challenges.